2012
DOI: 10.5194/acp-12-3147-2012
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and condensational growth to CCN sizes during a sustained pristine biogenic SOA event in a forested mountain valley

Abstract: Abstract.The Whistler Aerosol and Cloud Study (WACS 2010), included intensive measurements of trace gases and particles at two sites on Whistler Mountain. Between 6-11 July 2010 there was a sustained high-pressure system over the region with cloud-free conditions and the highest temperatures of the study. During this period, the organic aerosol concentrations rose from <1 µg m −3 to ∼6 µg m −3 . Precursor gas and aerosol composition measurements show that these organics were almost entirely of secondary biogen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
120
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 132 publications
(138 citation statements)
references
References 55 publications
(76 reference statements)
15
120
2
1
Order By: Relevance
“…In the NH, prolonged pristine periods generally occur only over continental regions above 60°N, such as in boreal Canada (32) and Russia (33), where aerosol is affected strongly by natural forest fire emissions. Here, CCN concentrations are highly variable, but generally range from 100 to 1,000 cm −3 .…”
Section: Resultsmentioning
confidence: 99%
“…In the NH, prolonged pristine periods generally occur only over continental regions above 60°N, such as in boreal Canada (32) and Russia (33), where aerosol is affected strongly by natural forest fire emissions. Here, CCN concentrations are highly variable, but generally range from 100 to 1,000 cm −3 .…”
Section: Resultsmentioning
confidence: 99%
“…Ambient and laboratory studies have shown that sulfuric acid participates in the first steps of new particle formation (Weber et al, 1996;Sihto et al, 2006;Riipinen et al, 2007;Kuang et al, 2008;Sipilä et al, 2010;Vehkamäki and Riipinen, 2012;Kulmala et al, 2013), but sulfuric acid condensation is not enough to reproduce particle growth rates observed in the ambient conditions (Kuang et al, 2010;Sipilä et al, 2010;Pierce et al, 2011Pierce et al, , 2012Riipinen et al, 2011Riipinen et al, , 2012Kulmala et al, 2013). Therefore other compounds, e.g., organics or ammonia/amines, are expected to be important in the early growth of freshly nucleated particles (O'Dowd et al, 2002;Smith et al, 2005Smith et al, , 2008Pierce et al, 2011;Riipinen et al, 2012;Vehkamäki and Riipinen, 2012;Kulmala et al, 2013).…”
Section: S a K Häkkinen Et Al: Semi-empirical Parameterization Ofmentioning
confidence: 99%
“…Organic compounds are known to aid in the growth of newly formed particles (∼ 1-2 nm diameter) to observable sizes (> 3 nm diameter; Boy et al, 2003;Kulmala et al, 2004;Verheggen et al, 2007;Laaksonen et al, 2008;Pierce et al, 2011;Yli-Juuti et al, 2011;Riccobono et al, 2012) and even further to a CCN-active size (> ∼ 70 nm diameter; Riipinen et al, 2011Riipinen et al, , 2012Pierce et al, 2012;Paasonen et al, 2013). Additionally, the oxidation products of terpenes may play a role in the initial stages of particle formation via stabilisation of the critical nucleus (Fan et al, 2006;Zhang et al, 2009;Metzger et al, 2010;Paasonen et al, 2010;Kulmala et al, 2013).…”
Section: Introductionmentioning
confidence: 99%